Murdered sleep: crime and aesthetics in France and England, 1850-1910 - Winchell, James (My University, 1988)
By 1850 the popular literature of crime in France and England had been highly visible to the public and salient in the minds of writers, artists and thinkers for some sixty years. The explosion of Gothic romances across Europe in the 1780's and 90's and the flowering of melodrama in the same period are other indications of the tectonic shift in popular consciousness and of a renewed interest in questions of transgression and legitimacy effected by the French revolution.After 1850, however, a new "literature of crime," emphasizing the relations between beauty and transgression, emerges in France and England. When disguised as Beauty, a nascent sense of modern or "deep" crime (in Balzac, De Quincey, Dickens, Poe and Baudelaire) deliberately exploits "the modes of error and truth" inherent in its status as a representation, while at the same time "falling away from literature" toward a critique of the "reality of the moment." "Aesthetic crime" presents the image of inter-subjective transgression as an action freed from pre-determined or monological interpretation.Beauty and Crime: by forcing the two together, as Baudelaire did in the guise of modern tragedy, as Huysmans, Schwob, Lorrain, Rops, Wilde and Dostoevsky did in hybrid, decadent and novelistic genres, the artist compounds the indeterminacy of the one with the over-determined nature of the other. In the period after 1850, no version of this issue is unambiguous; the "mystique of transgression" reveals persistent social and metaphysical concerns. This very forcing of the mask of transgression upon the face of beauty results, perhaps, in the characteristic fatigue of the period, borne along by the unhappy conscience that knows no rest, in the desolated cells of murdered sleep.
Thesis (Ph. D.)--University of Washington, 1988
Keywords: Theses--Comparative literature